Emotional Social Intelligence and Gardner’s Interpersonal and Intrapersonal Intelligence: : A Conceptual Analysis - K, Sindhu; Aravind, Ampili (Voices of Teachers and Teacher Educators, 2024)
Howard Gardner’s Theory of Multiple Intelligences, particularly interpersonal and intrapersonal intelligence, aligns with the concept of Emotional Social Intelligence (ESI). Interpersonal intelligence refers to the ability to understand others, akin to social intelligence, whereas intrapersonal intelligence, often termed self-psychological intelligence, is associated with emotional intelligence. Research studies indicate that socially oriented intelligence encompasses the capacity to assess social situations through the effective application of emotional intelligence. Social intelligence includes self-awareness and self-regulation as its key components. This paper explores the relationship between Gardner’s interpersonal and intrapersonal intelligence and the broader constructs of ESI.